Reactive Hip Arthritis and Avascular Necrosis After Severe COVID-19 Infection: A Case Report and Comprehensive Review of Literature - Fatima Alkindi; Shamma Al Nokhatha; Khalid Alseiari; Khalid A. Alnaqb (European Medical Journal Rheumatology)
COVID-19 has variable clinical presentations, severity, and multisystem involvement. Some patients have encountered arthralgia and myalgia symptoms. Reactive arthritis is an emerging musculoskeletal manifestation post-COVID-19 infection. The authors report a 29-year-old male, previously healthy, who developed acute left hip arthritis 8 weeks after recovering from severe COVID-19 pneumonia. It was associated with bilateral avascular necrosis of femoral heads, with medullary bone infarctions at both proximal tibias. Human leukocyte antigen-B27 was positive and synovial fluid culture, autoimmune workup, crystals, and infectious aetiologies were negative. The patient’s clinical condition improved with the use of non-steroidal anti-inflammatory drugs and physiotherapy. To the best of the authors’ knowledge, this is the first case reported of hip arthritis and avascular necrosis following the COVID-19 infection. In addition, the authors reviewed the literature for the reported reactive arthritis cases post-COVID-19 infection and management outcomes.